2008
DOI: 10.1075/ni.18.2.09tsa
|View full text |Cite
|
Sign up to set email alerts
|

“But I first… and then he kept picking”

Abstract: This study investigates the narrative skill of school-aged children with language impairment in Taiwan. Twelve children, 6 children with language impairment (LI) and 6 children with typical language development (TLD), aged from 8;0 to 9;5 participated in this study. They were asked to tell three personally experienced stories and the longest one was selected and coded along four dimensions, i.e., narrative structure, conjunction, referential strategies, and discourse context. The revision of the Chinese Narrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
1
8
1
Order By: Relevance
“…The group with LI produced fewer macrostructure elements (e.g., actions, settings) and exhibited lower usage of various expressions of internal state than the TD matches. Likewise, Tsai and Chang (2008) observed deficits in macrostructure in six Mandarin-speaking children with LI at 8 to 9 years old when compared to age matches. In addition, they found that general microstructure measures revealed group differences, including word productivity (i.e., TNW), lexical diversity (i.e., NDW), and syntactic complexity (i.e., MLU; Tsai & Chang, 2008).…”
Section: Narrative Skills In Mandarinmentioning
confidence: 76%
See 2 more Smart Citations
“…The group with LI produced fewer macrostructure elements (e.g., actions, settings) and exhibited lower usage of various expressions of internal state than the TD matches. Likewise, Tsai and Chang (2008) observed deficits in macrostructure in six Mandarin-speaking children with LI at 8 to 9 years old when compared to age matches. In addition, they found that general microstructure measures revealed group differences, including word productivity (i.e., TNW), lexical diversity (i.e., NDW), and syntactic complexity (i.e., MLU; Tsai & Chang, 2008).…”
Section: Narrative Skills In Mandarinmentioning
confidence: 76%
“…The likelihood of finding grammatical errors may be smaller in a narrative context in which children have much flexibility in choosing language expressions. In the following, we will review the three Mandarin narrative studies (Cheung, 2009;Tsai & Chang, 2008;Zhang, 2009) and see what differentiating measures have been found in Mandarin. Zhang (2009) compared two 4-year-old children with LI and their age matches.…”
Section: Narrative Skills In Mandarinmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies found differences on referential adequacy (RA) scores between children with and without LI (and Down syndrome in the case of Boudreau & Chapman, 2000). This method of analyzing referential cohesion is commonly used in research on TD children (Hickmann, 1991;Hickmann, Hendriks, Roland, & Jiang, 1996;Schneider & Dubé, 1997;Tsai & Chang, 2008). Using this method, any referring expression that is not fully adequate for its occurrence in a story is considered inadequate, and the percentage of RA is calculated as the number of adequate referring expressions divided by the total number of referring expressions.…”
Section: Studies Of Reference and Cohesion By Children With Language mentioning
confidence: 99%
“…Narrative skills are strongly associated with our conceptual and language development (Morrow, 1985;Vygotsky, 1962), connected to later literacy proficiency and academic achievement (Bishop and Edmundson, 1987;Boudreau and Hedberg, 1999;Chang, 2006;Hedberg and Westby, 1993;Westby, 1984;Wetherell et al, 2007) and socialization skills (Wetherell et al, 2007). Children experiencing language-learning difficulties are particularly susceptible to difficulties with the production of coherent and lucid narratives (Botting, 2002;Norbury and Bishop, 2003;Reilly et al, 2004;Tsai and Chang, 2008). They encounter particular difficulties with organizing stories and in using relevant vocabulary and suitable syntactic structures when generating narratives (Boudreau and Hedberg, 1999;Pearce et al, 2003;Reilly et al, 2004).…”
Section: Introductionmentioning
confidence: 97%